Alternative business models and entrepreneurship: The case of electric vehicles. (February 2018) - Nieuwenhuis, Paul
Electrification of the car is an inevitable trajectory; only battery electric vehicles (EVs) give the option – provided a zero carbon generating mix is developed – of ultimately zero carbon and zero emissions transport. Yet this means disruptive change to the existing automotive and energy business models covering all sections of the value chain, which provides entry points for new, entrepreneurial operators from outside the sector bringing with them new business models. We are entering a transition period, where some of these alternative business models are already seen to work and those of Autolib and Tesla are highlighted here. New electric vehicle (EV) business models need to extend beyond the boundaries of the business itself and should also include a consideration of context and environment, or 'regime' (Geels, 2002), particularly in the role of government. It should be emphasized that EV business models are dynamic, still emerging and are currently enjoying artificial market conditions due to widespread incentives. Private and public sector players are still exploring what their respective roles should be in future EV business models.